Morphometric Characters and Meristic Counts of Mastacembelus armatus (Lacebede, 1800) from Maruthur Anicut, Tirunelveli District, India - P, Raja; S, Muthukrishnan; Reneese, Joseph Antony (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present study highlights about morphometric measurement and meristic count of Mastacembelus armatus (Lacebede, 1800) collected from the Maruthur wetland ecosystem have been investigated with 23 specimens to observe the relationship between morphometric characters. Identification of species is an initial step in any research work and plays a vital role in the behavioural study. Morphometric character analysis and meristic counts are considered as simplest and authentic methods for fish species identification which is termed as morphological systematics. Fourteen different morphometric characters in percentage of total fish length (9 characters), head length (5 characters), and five different meristic counts (branched and unbranched rays) have been studied. The obtained result reveals that morphometric characters vary depending on the growth and size of the fish. However, the meristic counts were comparatively similar. All the characters show a positive correlation both in the percentage of total length and head length. The different morphometric and meristic counts of M. armatus have been analyzed for the population dynamics which includes taxonomy study and proper identification of fishes. The fin formula was calculated for some hard rays and soft rays. Therefore, this study supplement additional data for the identification of the fish species.